Effect of chemotherapy and different chemotherapeutic regimens on electrocardiographic parameters in breast cancer women: a retrospective and within-subject longitudinal study - She, Rui-ling; Liang, Xin-yu; Hu, Lei; Ma, Chen-yu; Mu, Li-yuan; Feng, Jun-han; Song, Jing-yu; Jiang, Zhi-yu; Li, Zhao-xing; Qu, Xiu-quan; Peng, Bai-qing; Wu, Kai-nan; et al. (Supportive care in cancer, 2025)
Background Descriptions of the effect of chemotherapy on all the electrocardiographic parameters in breast cancer women during chemotherapy are limited. Methods A retrospective and within-subject longitudinal study of the effect of chemotherapeutics and different chemotherapeutic regimens on electrocardiographic parameters was conducted in 948 breast cancer women who had completed chemotherapy with ECG recording at initial diagnosis and before each cycle of chemotherpy. Heart rate (HR), QRS interval, P-R interval, QRS axis, QT interval, QTc interval, and the incidence of QTc interval prolongation were analyzed. Age, body mass index (BMI), history of hypertension, diabetes, and coronary heart disease were also collected for further stratified study. Results Compared to initial diagnosis, changes in HR [74 (67, 82) bpm vs. 79 (73, 87)bpm], P-R interval [148 (136, 160) ms vs. 150 (138, 162) ms], QRS axis [41° (19.25°°, 60°) vs. 33° (15°, 53.75°)], QT interval [376 (358, 394) ms vs. 372 (354, 386) ms], QTc interval [417 (404, 431) ms vs. 426 (414, 436) ms], and incidence of QTc interval prolongation (9.6% vs. 15.8%) were all significant after chemotherapy, P < 0.001. There were statistically differences in HR, QRS axis, QTc interval, and the incidence of QTc interval prolongation between initial diagnosis and prechemotherapy of the last cycle under different age strata (≤ 45 years, 45 ~ 55 years, ≥ 55 years), different BMI range groups (18.5–22.9 kg/m 2 , 23–24.9 kg/m 2 , and 25–29.9 kg/m 2 ), and even in patients without history of hypertension, diabetes, or coronary heart disease, respectively, P < 0.05. Resting HR, QRS axis, and QTc interval between each cycle of TEC regimen were different, P < 0.001. Resting HR and QTc interval between different cycles of EC-T(H) regimen were different, P < 0.05. Compared to initial diagnosis, a longer QTc interval occurred from the third to the last cycle of TEC regimen, P < 0.05. Only QTc interval before the fifth cycle of EC-T(H) regimen was statistically different from that at initial diagnosis, P = 0.012. Conclusion Chemotherapy affects the ECG parameters of HR, P-R interval, QRS axis, QT interval, QTc interval, and QTc interval prolongation in early-stage breast cancer women during chemotherapy. Electrocardiographic parameters may be affected significantly by TEC regimen than by EC-T(H) or TC regimen. Trial registration Retrospectively registered.